N2O emission reduction catalyst and preparation method thereof

By using catalysts composed of CuO, ZnO, Al2O3, CoO and CeO2, and using active components of bispinite nanostructures, the problem of poor stability of existing catalysts at high temperatures and high aerial speeds is solved, and efficient N2O emission reduction is achieved.

CN119897116APending Publication Date: 2025-04-29SICHUAN SHUTAI CHEM TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411925273.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing catalysts are difficult to achieve high-temperature activity stability and high aerial speed at the same time, and cannot effectively control and eliminate N2O emissions.

Method used

An N2O emission reduction catalyst composed of CuO, ZnO, Al2O3, CoO and CeO2 is used, and the active components of CuAl2O4 and ZnCo2O4 bispinite nanostructures are formed by specific preparation methods, including ball milling and press molding.

Benefits of technology

The catalyst has achieved high-temperature activity stability and high-speed operation ability, can effectively reduce N2O emissions, and has good water resistance and high-temperature sintering resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897116A_ABST
    Figure CN119897116A_ABST
Patent Text Reader

Abstract

The invention discloses an N2O emission reduction catalyst and a preparation method thereof. The catalyst comprises CuO, ZnO, Al2O3, CoO and CeO2. An active component with a CuAl2O4 and ZnCo2O4 double-spinel nanostructure is synthesized, oxygen ions in the spinel compound are arranged according to cubic close packing, tetrahedral gaps are filled with divalent cations, octahedral gaps are filled with trivalent cations, the structure is stable, the high-temperature stability is high, and the CuAl2O4 and ZnCo2O4 double-spinel nanostructure can be used as a catalyst active component, so that the CuAl2O4 and ZnCo2O4 double-spinel nanostructure can be used as a catalyst. The activity and the activity stability of the catalyst are high, and the water resistance is strong; the active component and the modified carrier are uniformly mixed and then molded, the active component is uniformly dispersed, and the high-temperature sintering resistance is high; the catalyst is calcined at high temperature again after being formed, mutual fusion of the active components and the carrier is enhanced, the catalyst has good high-temperature thermal stability, and long-term stable operation of the catalyst is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of industrial catalysts, and in particular to a N2O emission reduction catalyst and a preparation method thereof. Background Art

[0002] At present, the main greenhouse gases in the atmosphere include CO2, CH4, N2O, HFCs, PFCs and SF6. Among them, N2O is a trace gas, and its contribution to the greenhouse effect is 21 times that of CH4. At the same time, the global warming potential (GWP) of N2O is 310 times that of CO2. Every doubling of the atmospheric concentration of N2O will cause global warming of 0.3℃. In addition, N2O is very stable and has a residence time of up to 120 years. Therefore, how to effectively control and eliminate N2O has become an important environmental issue of common concern to the world. The main cause of N2O is industrial emissions.

[0003] In order to remove N2O from industrial emissions, the prior art uses solutions such as the use of zirconium-cerium mixed oxide catalysts (CN1720092A), the use of cobalt-magnesium and cobalt-iron compound catalysts (CN1398196A, CN1440309A), the use of zirconium catalysts on refractory oxide carriers (CN1274297A), the use of cobalt mixed oxide catalysts on molecular sieves (CN1011905162A), and the use of metal oxide catalysts such as copper, zinc, iron, nickel, and manganese based on porous ceramic carriers (CN102962073A). However, all of the above studies can only meet some harsh conditions, such as zirconium and other catalysts can meet high-speed operation, but poor high-temperature stability. Magnesium, cobalt and other catalysts can achieve high-temperature activity stability, but the high-speed operation is low. Summary of the invention

[0004] In view of this, the present application provides a N2O emission reduction catalyst and a preparation method thereof, aiming to solve the problem that existing catalysts cannot achieve high temperature activity stability and high space velocity operation at the same time.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, the present invention provides a N2O emission reduction catalyst, wherein the catalyst comprises CuO, ZnO, Al2O3, CoO, and CeO2.

[0007] In some embodiments, the catalyst comprises, by mass percentage, 15% to 25% CuO, 3% to 8% ZnO, 50% to 70% Al2O3, 5% to 15% Co2O3, and 5% to 15% CeO2. ;

[0008] In a second aspect, the present invention provides a method for preparing a N2O emission reduction catalyst, comprising:

[0009] Desalted water is provided, and the pH is adjusted to 7-8 to obtain a first solution; a copper nitrate-aluminum nitrate mixed solution and a sodium carbonate solution are provided respectively, and the copper nitrate-aluminum nitrate mixed solution and the sodium carbonate solution are added to the first solution in parallel to obtain a second solution, and then subjected to a second stirring aging, a first filtration, a first washing, a first drying and a first calcination to obtain a CuAl2O4 spinel powder;

[0010] Provide desalted water, adjust the pH to 8-9, and obtain a third solution; provide a zinc nitrate-cobalt nitrate mixed solution and a sodium carbonate solution respectively, add the zinc nitrate-cobalt nitrate mixed solution and the sodium carbonate solution into the third solution in a second parallel flow to obtain a fourth solution, and then perform a fourth stirring aging, a second filtration, a second washing, a second drying, and a second calcination to obtain a ZnCo2O4 spinel powder;

[0011] Provide a Ce(NO3)3 solution, slowly drop an alkali solution into the Ce(NO3)3 solution until the pH reaches 9-10, then add activated alumina powder under the sixth stirring, let stand, then filter for a third time, dry for a third time and calcine for a third time to obtain a CeO2-modified Al2O3 carrier;

[0012] The CuAl2O4 spinel powder, the ZnCo2O4 spinel powder, the CeO2-modified Al2O3 carrier, the binder and the graphite are ball-milled and sieved together to obtain a catalyst material;

[0013] The catalyst material is mixed with water, pressed, steam cured, and calcined for the fourth time to obtain a finished catalyst product.

[0014] In some embodiments, when preparing CuAl2O4 spinel powder, sodium carbonate is used to adjust the pH to 7-8; and / or

[0015] When preparing ZnCo2O4 spinel powder, adjust the pH to 8-9 with sodium carbonate; and / or

[0016] The pH of the second solution is 7 to 7.5; and / or

[0017] The pH of the fourth solution is 8.5 to 9;

[0018] In some embodiments, the method for preparing a copper nitrate-aluminum nitrate mixed solution comprises taking copper nitrate trihydrate and aluminum nitrate nonahydrate and adding them to desalted water to obtain a Cu(NO3)2-Al(NO3)3 mixed solution; the first metal concentration in the Cu(NO3)2-Al(NO3)3 mixed solution is C1, the molar ratio of Cu to Al in the Cu(NO3)2-Al(NO3)3 mixed solution is M1, and the Cu(NO3)2-Al(NO3)3 mixed solution is heated to T1; and / or

[0019] Providing desalted water and sodium carbonate, adding sodium carbonate to the desalted water to obtain a Na2CO3 solution; the concentration of the Na2CO3 solution is C2, and the Na2CO3 solution is heated to T2; and / or

[0020] The time of the first parallel addition is t1, the speed of the first stirring during the first parallel addition is v2, the reaction temperature during the first parallel addition is T2, the temperature is maintained at T3 after the first parallel addition, the speed of the second stirring aging is v3, the time of the second stirring aging is t2, the first washing is until the Na content is lower than C3, the temperature of the first drying is T4, the time of the first drying is t3, the temperature of the first calcination is T5, and the time of the first calcination is t4; and / or

[0021] The method for obtaining a zinc nitrate-cobalt nitrate mixed solution comprises taking zinc nitrate hexahydrate and cobalt nitrate hexahydrate and adding them to desalted water to obtain a Zn(NO3)2-Co(NO3)2 mixed solution; the concentration of the second metal in the Zn(NO3)2-Co(NO3)2 mixed solution is C4, the molar ratio of Zn to Co in the Zn(NO3)2-Co(NO3)2 mixed solution is M2, and the Zn(NO3)2-Co(NO3)2 mixed solution is heated to T6; and / or

[0022] Providing desalted water and sodium carbonate, adding sodium carbonate to the desalted water to obtain a Na2CO3 solution; the concentration of the Na2CO3 solution is C5, and heating the Na2CO3 solution to T7; and / or

[0023] The time of the second parallel addition is t5, the speed of the third stirring during the second parallel addition is v5, the reaction temperature during the second parallel addition is T7, the temperature is maintained to T8 after the second parallel addition is completed, the speed of the fourth stirring aging is v6, the time of the fourth stirring aging is t6, the second washing is until the Na content is lower than C6, the temperature of the second drying is T9, the time of the second drying is t7, the temperature of the second calcination is T10, and the time of the second calcination is t8; and / or

[0024] Adding cerium nitrate hexahydrate to desalted water to obtain a Ce(NO3)3 solution; the concentration of the third metal in the Ce(NO3)3 solution is C7, and the Ce(NO3)3 solution is heated to T13; and / or

[0025] During the process of adding the alkali solution, a fifth stirring is performed, the speed of the fifth stirring is v7, the speed of the sixth stirring is v8, the standing time is t9, the temperature of the third drying is T11, the time of the third drying is t10, the temperature of the third calcination is T12, and the time of the third calcination is t11; and / or

[0026] Curing the pressed catalyst sample under P pressure steam conditions for T12; and / or

[0027] The temperature of the fourth calcination is T14, and the time of the fourth calcination is t13;

[0028] In some embodiments, C1 is 0.9 mol / L to 1.1 mol / L; and / or

[0029] M1 is 0.4 to 0.5; and / or

[0030] T1 is 60°C to 65°C; and / or

[0031] C2 is 0.6-0.8 mol / L; and / or

[0032] T2 is 60°C to 65°C; and / or

[0033] t1 is 20 to 30 minutes; and / or

[0034] v2 is 300 rpm to 500 rpm; and / or

[0035] T2 is 60°C to 65°C; and / or

[0036] T3 is 60°C to 65°C; and / or

[0037] v3 is 50 rpm to 100 rpm; and / or

[0038] t2 is 60 min to 120 min; and / or

[0039] C3 is 100 mg / kg; and / or

[0040] T4 is 100°C to 120°C; and / or

[0041] t3 is 12h to 24h; and / or

[0042] T5 is 800°C to 900°C; and / or

[0043] t4 is 2h to 6h; and / or

[0044] C4 is 0.9 mol / L to 1.1 mol / L; and / or

[0045] M2 is 0.5 to 0.7; and / or

[0046] T6 is 60°C to 65°C; and / or

[0047] C5 is 0.6 mol / L to 0.8 mol / L; and / or

[0048] T7 is 60℃~65℃; and / or

[0049] t5 is 5 to 10 minutes; and / or

[0050] v5: 300 rpm ~ 500 rpm

[0051] T7 is 60℃~65℃; and / or

[0052] T8 is 60°C to 65°C; and / or

[0053] v6 is 50 rpm to 100 rpm; and / or

[0054] t6 is 60 min to 120 min; and / or

[0055] C6 100 mg / kg; and / or

[0056] T9 is 100°C to 120°C; and / or

[0057] t7 is 12h to 24h; and / or

[0058] T10 is 800°C to 900°C; and / or

[0059] t8 is 2h to 6h; and / or

[0060] C7 is 0.4 mol / L to 0.5 mol / L; and / or

[0061] T13 is 60℃~65℃; and / or

[0062] v7 is 100 rpm to 200 rpm; and / or

[0063] V8 is 300 rpm to 500 rpm; and / or

[0064] t9 is 10h to 14h; and / or

[0065] T11 is 100°C to 140°C; and / or

[0066] t10 is 8h to 12h; and / or

[0067] T12 is 400°C to 600°C; and / or

[0068] t11 is 4h to 6h; and / or

[0069] P is 0.8MPa to 1.2MPa; and / or

[0070] t12 is 12h to 24h; and / or

[0071] T14 is 1000°C to 1100°C; and / or

[0072] t13 is 4h~6h;

[0073] In some embodiments, the mass ratio of CeO2:Al2O3 is 2:8; and / or

[0074] The mass ratio of CuAl2O4 spinel powder, ZnCo2O4 spinel powder, CeO2 modified Al2O3 carrier, binder and graphite is 35-45:10-20:40-55:2:3; and / or

[0075] The mass ratio of catalyst material to water is 100:3-5; and / or

[0076] The alkali solution is ammonia water, and the concentration of ammonia water is 10% to 20%; and / or

[0077] The mesh size of the sieve is 180-220 mesh;

[0078] In some embodiments, the adhesive includes one or more of kapok, polyvinyl alcohol, and polyester fiber;

[0079] In some embodiments, the average particle size of the CuAl2O4 spinel is 10 nm to 50 nm; and / or

[0080] The average particle size of ZnCo2O4 spinel is 30nm~100nm.

[0081] Beneficial effects:

[0082] In the present application, an active component having a CuAl2O4 and ZnCo2O4 double spinel nanostructure is synthesized. In this type of spinel compound, oxygen ions are arranged in a cubic closest packing, divalent cations are filled in tetrahedral voids, and trivalent cations are filled in octahedral voids. The structure is stable and has strong high-temperature stability. As an active component of a catalyst, the catalyst has high activity and activity stability and strong water resistance. The active component is mixed evenly with a modified carrier and then molded. The active component is evenly dispersed and has strong resistance to high-temperature sintering. After the catalyst is molded, it is calcined at a high temperature again, which strengthens the mutual fusion of the active component and the carrier. It has good high-temperature thermal stability and is conducive to the long-term stable operation of the catalyst. The catalyst preparation process of the present application is simple, has strong operability, and is very easy to realize industrial production. No precious metal raw materials are used, the price is appropriate, and it has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0083] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0084] Figure 1 is a flow chart of a method for preparing a N2O emission reduction catalyst provided in an embodiment of the present application;

[0085] Figure 2 It is a device for evaluating the activity of the catalysts in the examples and comparative examples of the present application. DETAILED DESCRIPTION

[0086] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0087] In this application, further, in the description of this application, the term "including" means "including but not limited to." The terms first, second, third, etc. are used merely as labels and do not impose numerical requirements or establish a sequence.

[0088] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0089] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0090] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0091] The technical solution of this application is as follows:

[0092] In a first aspect, an embodiment of the present application provides a N2O emission reduction catalyst, wherein the catalyst includes CuO, ZnO, Al2O3, CoO, and CeO2.

[0093] The N2O emission reduction catalyst of the present application has active components of CuAl2O4 and ZnCo2O4 double spinel nanostructures. In this type of spinel compound, oxygen ions are arranged in a cubic closest packing, divalent cations are filled in tetrahedral voids, and trivalent cations are filled in octahedral voids. The structure is stable and has strong high-temperature stability. As the active component of the catalyst, the catalyst has high activity and activity stability, strong water resistance, and can operate for a long time under high temperature conditions.

[0094] In some embodiments, the catalyst comprises, by mass percentage, 15% to 25% CuO, 3% to 8% ZnO, 50% to 70% Al2O3, 5% to 15% Co2O3, and 5% to 15% CeO2.

[0095] Further, by mass percentage, the catalyst includes 15% to 25% CuO, preferably 17% to 23% CuO, more preferably 19% to 21% CuO; 3% to 8% ZnO, preferably 4% to 7% ZnO, more preferably 5% to 6% ZnO; 50% to 65% Al2O3, preferably 53% to 62% Al2O3, more preferably 55% to 60% Al2O3; 5% to 15% Co2O3, preferably 7% to 13% Co2O3, more preferably 9% to 12% Co2O3. 5% to 15% CeO2, preferably 7% to 13% CeO2, more preferably 9% to 12% CeO2.

[0096] In some embodiments, the average particle size of CuAl2O4 spinel is 10nm to 50nm, for example, it can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc. The structure is stable within the average particle size range and can be used for high-temperature operation for a long time without agglomeration.

[0097] In some embodiments, the average particle size of ZnCo2O4 spinel is 30nm to 100nm, for example, it can be 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, etc. The structure is stable within the average particle size range and can be used for high-temperature operation for a long time without agglomeration.

[0098] See also Figure 1 In a second aspect, the present application provides a method for preparing a N2O emission reduction catalyst, comprising:

[0099] S01, providing desalted water, adjusting the pH to 7-8, obtaining a first solution; respectively providing a copper nitrate-aluminum nitrate mixed solution and a sodium carbonate solution, adding the copper nitrate-aluminum nitrate mixed solution and the sodium carbonate solution into the first solution in parallel, obtaining a second solution, and then performing a second stirring aging, a first filtration, a first washing, a first drying and a first calcination to obtain a CuAl2O4 spinel powder;

[0100] S02, providing desalted water, adjusting the pH to 8-9, and obtaining a third solution; respectively providing a zinc nitrate-cobalt nitrate mixed solution and a sodium carbonate solution, and adding the zinc nitrate-cobalt nitrate mixed solution and the sodium carbonate solution to the third solution in parallel for a second time to obtain a fourth solution, and then performing a fourth stirring aging, a second filtration, a second washing, a second drying, and a second calcination to obtain a ZnCo2O4 spinel powder;

[0101] S03, providing a Ce(NO3)3 solution, slowly dropping an alkali solution into the Ce(NO3)3 solution until the pH reaches 9-10, then adding activated alumina powder under the sixth stirring, standing, then filtering for the third time, drying for the third time and calcining for the third time to obtain a CeO2-modified Al2O3 carrier;

[0102] S04, ball-milling CuAl2O4 spinel powder, ZnCo2O4 spinel powder, CeO2-modified Al2O3 carrier, binder and graphite together and sieving to obtain a catalyst material;

[0103] S05. Mixing the catalyst material with water, pressing, steam curing, and calcining for the fourth time to obtain a finished catalyst product.

[0104] In the present application, the CeO2-modified carrier has better thermal stability, because cerium dioxide has a high melting point and high heat capacity, which can effectively improve the high-temperature thermal stability of the alumina matrix carrier; in addition, cerium dioxide can capture mobile atoms at high temperatures, which can effectively prevent the aggregation and growth of the active component particles of the catalyst, thereby maintaining the activity stability of the catalyst, which is more conducive to the long-term operation of the catalyst at high temperatures.

[0105] In the S01:

[0106] In some embodiments, sodium carbonate is used to adjust the pH to 7-8, for example, the pH may be 7, 7.2, 7.3, 7.5, 7.6, 7.8, 8, etc.

[0107] It will be appreciated that potassium carbonate may also be used to adjust the pH.

[0108] In some embodiments, the preparation method of a copper nitrate-aluminum nitrate mixed solution includes taking copper nitrate trihydrate and aluminum nitrate nonahydrate and adding them to desalted water to obtain a Cu(NO3)2-Al(NO3)3 mixed solution; the first metal concentration in the Cu(NO3)2-Al(NO3)3 mixed solution is C1, the molar ratio of Cu to Al in the Cu(NO3)2-Al(NO3)3 mixed solution is M1, and the Cu(NO3)2-Al(NO3)3 mixed solution is heated to T1.

[0109] Further, C1 is 0.9 mol / L to 1.1 mol / L, for example, 0.9 mol / L, 0.95 mol / L, 1 mol / L, 1.05 mol / L, 1.1 mol / L, etc.;

[0110] M1 is 0.4 to 0.5, for example, 0.4, 0.42, 0.45, 0.48, 0.5, etc.;

[0111] T1 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.

[0112] In some embodiments, desalted water and sodium carbonate are provided, and sodium carbonate is added to the desalted water to obtain a Na2CO3 solution; the concentration of the Na2CO3 solution is C2, and the Na2CO3 solution is heated to T2.

[0113] Further, C2 is 0.6 to 0.8 mol / L, for example, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.75 mol / L, 0.78 mol / L, 0.8 mol / L, etc.;

[0114] T2 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.

[0115] In some embodiments, the time of the first parallel addition is t1, the speed of the first stirring during the first parallel addition is v2, the reaction temperature during the first parallel addition is T2, the temperature is maintained at T3 after the first parallel addition, the speed of the second stirring aging is v3, the time of the second stirring aging is t2, the first washing is until the Na content is lower than C3, the temperature of the first drying is T4, the time of the first drying is t3, the temperature of the first calcination is T5, and the time of the first calcination is t4.

[0116] t1 is 20 min to 30 min, for example, 20 min, 22 min, 25 min, 26 min, 28 min, 30 min, etc.;

[0117] v2 is 300 rpm to 500 rpm, for example, it can be 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, etc.

[0118] T2 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.;

[0119] T3 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.;

[0120] v3 is 50 rpm to 100 rpm, for example, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm, etc.;

[0121] t2 is 60 min to 120 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.;

[0122] C3: 100 mg / kg;

[0123] T4 is 100°C to 120°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C, etc.;

[0124] t3 is 12h to 24h, for example, it can be 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.;

[0125] T5 is 800°C to 900°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, etc.;

[0126] t4 is 2 h to 6 h, for example, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, or 6 h.

[0127] In some embodiments, the pH of the second solution is 7 to 7.5, for example, 7, 7.1, 7.2, 7.3, 7.4, 7.5, etc.

[0128] In some embodiments, the average particle size of CuAl2O4 spinel is 10nm to 50nm, for example, it can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc. The structure is stable within the average particle size range and can be used for high-temperature operation for a long time without agglomeration.

[0129] In the S02:

[0130] In some embodiments, sodium carbonate is used to adjust the pH to 8-9, for example, the pH may be 8, 8.2, 8.5, 8.6, 8.8, 9, etc.

[0131] It will be appreciated that potassium carbonate may also be used to adjust the pH.

[0132] In some embodiments, the method for obtaining a zinc nitrate-cobalt nitrate mixed solution includes taking zinc nitrate hexahydrate and cobalt nitrate hexahydrate and adding them to desalted water to obtain a Zn(NO3)2-Co(NO3)2 mixed solution; the second metal concentration in the Zn(NO3)2-Co(NO3)2 mixed solution is C4, the molar ratio of Zn to Co in the Zn(NO3)2-Co(NO3)2 mixed solution is M2, and the Zn(NO3)2-Co(NO3)2 mixed solution is heated to T6.

[0133] Further, C4 is 0.9 mol / L to 1.1 mol / L, for example, 0.9 mol / L, 0.95 mol / L, 1 mol / L, 1.05 mol / L, 1.1 mol / L, etc.;

[0134] M2 is 0.5 to 0.7, for example, 0.5, 0.55, 0.6, 0.65, 0.7, etc.;

[0135] T6 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.

[0136] In some embodiments, desalted water and sodium carbonate are provided, and sodium carbonate is added to the desalted water to obtain a Na2CO3 solution; the concentration of the Na2CO3 solution is C5, and the Na2CO3 solution is heated to T7.

[0137] Further, C5 is 0.6 mol / L to 0.8 mol / L, for example, 0.6 mol / L, 0.65 mol / L, 0.68 mol / L, 0.7 mol / L, 0.75 mol / L, 0.8 mol / L, etc.;

[0138] T7 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.

[0139] In some embodiments, the time for the second parallel addition is t5, the speed of the third stirring during the second parallel addition is v5, the reaction temperature during the second parallel addition is T7, the temperature is maintained at T8 after the second parallel addition is completed, the speed of the fourth stirring aging is v6, the time of the fourth stirring aging is t6, the second washing is until the Na content is lower than C6, the temperature of the second drying is T9, the time of the second drying is t7, the temperature of the second calcination is T10, and the time of the second calcination is t8.

[0140] t5 is 5 min to 10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc.;

[0141] v5 is 300 rpm to 500 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, etc.;

[0142] T7 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.;

[0143] T8 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.;

[0144] v6 is 50 rpm to 100 rpm, for example, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm, etc.;

[0145] t6 is 60 min to 120 min, for example, it can be 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.;

[0146] C6: 100 mg / kg;

[0147] T9 is 100°C to 120°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C, etc.;

[0148] t7 is 12h to 24h, for example, it can be 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.;

[0149] T10 is 800°C to 900°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, etc.;

[0150] t8 is 2 h to 6 h, for example, it can be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, etc.

[0151] In some embodiments, the pH of the fourth solution is 8.5-9, for example, 8.5, 8.6, 8.7, 8.8, 8.9, 9, etc.

[0152] In some embodiments, the average particle size of ZnCo2O4 spinel is 30nm to 100nm, for example, it can be 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, etc. The structure is stable within the average particle size range and can be used for high-temperature operation for a long time without agglomeration.

[0153] In said S03:

[0154] In some embodiments, cerium nitrate hexahydrate is added to desalted water to obtain a Ce(NO3)3 solution; the concentration of the third metal in the Ce(NO3)3 solution is C7, and the Ce(NO3)3 solution is heated to T13.

[0155] Further, C7 is 0.4 mol / L to 0.5 mol / L, for example, 0.4 mol / L, 0.42 mol / L, 0.45 mol / L, 0.47 mol / L, 0.5 mol / L, etc.;

[0156] T13 is 60°C to 65°C, for example, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.

[0157] In some embodiments, the mass ratio of CeO2:Al2O3 is 2:8.

[0158] In some embodiments, the alkali solution is aqueous ammonia.

[0159] Furthermore, the concentration of the ammonia water is 10% to 20%, for example, 10%, 12%, 15%, 16%, 18%, 20%, etc.

[0160] In some embodiments, the fifth stirring is performed during the addition of alkali solution, the speed of the fifth stirring is v7, the speed of the sixth stirring is v8, the standing time is t9, the temperature of the third drying is T11, the time of the third drying is t10, the temperature of the third calcination is T12, and the time of the third calcination is t11.

[0161] Further, v7 is 100 rpm to 200 rpm, for example, 100 rpm, 120 rpm, 150 rpm, 160 rpm, 180 rpm, 200 rpm, etc.;

[0162] V8 is 300 rpm to 500 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, etc.;

[0163] t9 is 10h to 14h, for example, 10h, 11h, 12h, 13h, 14h, etc.;

[0164] T11 is 100°C to 140°C, for example, 100°C, 105°C, 110°C, 120°C, 130°C, 140°C, etc.;

[0165] t10 is 8h to 12h, for example, 8h, 9h, 10h, 11h, 12h, etc.;

[0166] T12 is 400°C to 600°C, for example, 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C, etc.;

[0167] t11 is 4 h to 6 h, for example, it can be 4 h, 4.5 h, 4.8 h, 5 h, 5.5 h, 6 h, etc.

[0168] In said S04:

[0169] In some embodiments, the adhesive includes one or more of kapok, polyvinyl alcohol, and polyester fiber.

[0170] In some embodiments, the mass ratio of CuAl2O4 spinel powder, ZnCo2O4 spinel powder, CeO2 modified Al2O3 carrier, binder and graphite is 35-45:10-20:40-55:2:3, for example, it can be 35:10-20:40-55:2:3, 38:10-20:40-55:2:3, 40:10-20:40-55:2:3, 42:10-20:40-55:2:3, 45:10-20:40-55:2:3, 35-45:10:40-55:2:3, :2:3, 35~45:12:40~55:2:3, 35~45:15:40~55:2:3, 35~45:18:40~55:2:3, 35~45:20:40~55:2:3, 35~45:10~20:40:2:3, 35~45:10~20:42:2:3, 35~45:10~20:48:2:3, 35~45:10~20:50:2:3, 35~45:10~20:52:2:3, 35~45:10~20:55:2:3, etc.

[0171] In some embodiments, the mesh size of the sieving is 180 mesh to 220 mesh, for example, it can be 180 mesh, 185 mesh, 190 mesh, 195 mesh, 200 mesh, 205 mesh, 210 mesh, 215 mesh, 220 mesh, etc.

[0172] In said S05:

[0173] In some embodiments, the mass ratio of the catalyst material to water is 100:3-5, for example, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, etc.

[0174] In some embodiments, the catalyst material is mixed with water and then a dry powder granulator is used to prepare qualified particles, which are then pressed into a Φ11×9×2mm black seven-hole cylinder or a Φ9×9mm black four-hole four-slot cylinder.

[0175] In some embodiments, the compressed catalyst sample is maintained under P pressure steam conditions for t12.

[0176] Furthermore, P is 0.8 MPa to 1.2 MPa, for example, it can be 0.8 MPa, 0.9 MPa, 1 MPa, 1.1 MPa, 1.2 MPa, etc.

[0177] t12 is 12 h to 24 h, for example, it can be 12 h, 15 h, 18 h, 20 h, 22 h, 24 h, etc.

[0178] In some embodiments, the temperature of the fourth calcination is T14, and the time of the fourth calcination is t13.

[0179] Further, T14 is 1000°C to 1100°C, for example, 1000°C, 1050°C, 1100°C, etc.;

[0180] t13 is 4 h to 6 h, for example, it can be 4 h, 4.5 h, 4.8 h, 5 h, 5.5 h, 6 h, etc.

[0181] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0182] Example 1

[0183] This embodiment provides a N2O emission reduction catalyst, which includes, by mass percentage, 19% CuO, 5.8% ZnO, 56.7% Al2O3, 10.5% Co2O3, and 8% CeO2.

[0184] The preparation method of the N2O emission reduction catalyst comprises:

[0185] Step 1: Preparation of CuAl2O4 spinel powder

[0186] Step 1.1, preparation of copper nitrate-aluminum nitrate solution: 177g copper nitrate trihydrate and 546g aluminum nitrate nonahydrate are added to 1.6L desalted water to obtain a Cu(NO3)2-Al(NO3)3 mixed solution with a metal concentration of 1.0mol / L, wherein the molar ratio of Cu to Al is 0.5, and the solution is heated to 63°C for standby use;

[0187] Step 1.2, preparation of sodium carbonate solution: 300 g of sodium carbonate was added to 3.5 L of desalted water to obtain a Na2CO3 concentration of 0.75 mol / L, and the solution was heated to 63°C for later use;

[0188] Step 1.3, preparation of CuAl2O4: add 0.5L of desalted water into the reactor, and adjust the pH of the solution to 7 with sodium carbonate; add the copper nitrate-aluminum nitrate solution prepared in step 1.1 and the sodium carbonate solution prepared in step 1.2 into the reactor in parallel, control the stirring speed at 400 rpm during the neutralization process, control the pH of the solution at 7.2, add the flow time for 25min, and the reaction temperature is 63°C; after the solutions in step 1.1 and step 1.2 are added, continue to maintain the reaction temperature, stir and age for 90min, and the stirring speed during stirring and aging is 75 rpm.

[0189] Step 1.4: After aging is completed, the material is filtered and washed until the Na content in the material is less than 100 mg / kg;

[0190] Step 1.5, the washed material is dried at 110°C for 18 hours, and then heated to 850°C and calcined for 4 hours to obtain CuAl2O4 spinel powder for use;

[0191] Step 2: Preparation of ZnCo2O4 spinel powder

[0192] Step 2.1, preparation of zinc nitrate-cobalt nitrate solution: 69.3 g of zinc nitrate hexahydrate and 114 g of cobalt nitrate hexahydrate were added to 450 mL of desalted water to obtain a mixed solution of Zn(NO3)2-Co(NO3)2 with a metal concentration of 1.0 mol / L, wherein the molar ratio of Zu to Co is 0.6, and the solution was heated to 63°C for standby use;

[0193] Step 2.2, preparation of sodium carbonate solution: Preparation of sodium carbonate solution: Take 200g of sodium carbonate and add it into 2.2L of desalted water to obtain a concentration of Na2CO3 of 0.75mol / L, and heat it to 63°C for use;

[0194] Step 2.3, preparation of ZnCo2O4: add 250mL of desalted water into the reactor, and adjust the pH of the solution to 8 with sodium carbonate; add the zinc nitrate-cobalt nitrate solution prepared in step 2.1 and the sodium carbonate solution prepared in step 2.2 into the reactor in parallel, control the stirring speed at 400 rpm during the neutralization process, control the pH of the solution at 8.8, add the feeding time for 7min, and the reaction temperature for 63°C; after the solutions in step 2.1 and step 2.2 are added, continue to maintain the reaction temperature and stir and age for 90min;

[0195] Step 2.4: After aging, the material is filtered and washed until the Na content in the material is less than 100 mg / kg;

[0196] Step 2.5, the washed material is dried at 110°C for 18 hours, and then heated to 850°C and calcined for 4 hours to obtain ZnCo2O4 spinel structure powder for use;

[0197] Step 3: Preparation of CeO2-modified Al2O3 carrier

[0198] Step 3.1, take 200g of cerium nitrate hexahydrate and add it to 950mL of desalted water to obtain a Ce(NO3)3 metal concentration of 0.46mol / L, and heat it to 63°C for use;

[0199] Step 3.2, slowly add 1.5L of 20% ammonia water to the above solution, control the stirring speed at 150 rpm during the dropping process, and add ammonia water until the pH reaches 9; then add 320g of activated alumina powder under stirring; let it stand for 12h after adding alumina powder;

[0200] Step 3.3, filter the material after standing, and dry the filter cake at 120°C for 10 hours, then heat it to 500°C and calcine it for 5 hours to obtain CeO2-modified Al2O3 for later use;

[0201] Step 4: Preparation of catalyst powder

[0202] The CuAl2O4 spinel powder, ZnCo2O4 spinel powder, CeO2 modified Al2O3 carrier, polyvinyl alcohol and graphite prepared above were ball-milled together in a ratio of 44:16:40:2:3 until all the particles passed 200 meshes to obtain a catalyst material for later use;

[0203] Step 5: Catalyst molding

[0204] The catalyst material obtained above and water were mixed evenly at a ratio of 100:5, and qualified particles were prepared using a dry powder granulator, and finally pressed into a Φ11×9×2mm black seven-hole cylinder;

[0205] The pressed Φ11×9×2mm black seven-hole cylinder was cured under 1Mpa pressure steam for 18h;

[0206] Step 6: Catalyst Calcination

[0207] The pressed catalyst was calcined at 1050°C for 5 hours to obtain the finished catalyst.

[0208] Example 2

[0209] This embodiment provides a N2O emission reduction catalyst, which includes, by mass percentage, 15.0% CuO, 4.5% ZnO, 60.5% Al2O3, 9.5% Co2O3, and 10.5% CeO2.

[0210] The preparation method of the N2O emission reduction catalyst comprises:

[0211] Step 1: Preparation of CuAl2O4 spinel powder

[0212] Step 1.1, preparation of copper nitrate-aluminum nitrate solution: 140g copper nitrate trihydrate and 434g aluminum nitrate nonahydrate are added to 1.4L desalted water to obtain a Cu(NO3)2-Al(NO3)3 mixed solution with a metal concentration of 1.1mol / L, wherein the molar ratio of Cu to Al is 0.5, and the solution is heated to 63°C for standby use;

[0213] Step 1.2, preparation of sodium carbonate solution: 300 g of sodium carbonate was added to 4.5 L of desalted water to obtain a Na2CO3 concentration of 0.60 mol / L, and the solution was heated to 63°C for later use;

[0214] Step 1.3, preparation of CuAl2O4: add 0.5L of desalted water into the reactor, and adjust the pH value of the solution to 7.2 with sodium carbonate; add the copper nitrate-aluminum nitrate solution prepared in step 1.1 and the sodium carbonate solution prepared in step 1.2 into the reactor in parallel, control the stirring speed at 400 rpm during the neutralization process, control the pH value of the solution at 7.5, add the flow time for 25min, and the reaction temperature for 63°C; after the solutions in step 1.1 and step 1.2 are added, continue to maintain the reaction temperature, stir and age for 90min, and the stirring speed during stirring and aging is 75 rpm;

[0215] Step 1.4: After aging is completed, the material is filtered and washed until the Na content in the material is less than 100 mg / kg;

[0216] Step 1.5, the washed material is dried at 110°C for 18 hours, and then heated to 850°C and calcined for 4 hours to obtain CuAl2O4 spinel powder for use;

[0217] Step 2: Preparation of ZnCo2O4 spinel powder

[0218] Step 2.1, preparation of zinc nitrate-cobalt nitrate solution: 54 g of zinc nitrate hexahydrate and 106 g of cobalt nitrate hexahydrate are added to 500 L of desalted water to obtain a mixed solution of Zn(NO3)2-Co(NO3)2 with a metal concentration of 0.9 mol / L, wherein the molar ratio of Zu to Co is 0.5, and the mixture is heated to 63°C for standby use;

[0219] Step 2.2, preparation of sodium carbonate solution: Preparation of sodium carbonate solution: Take 200g of sodium carbonate and add it into 3.0L of desalted water to obtain a concentration of Na2CO3 of 0.6mol / L, and heat it to 63°C for use;

[0220] Step 2.3, preparation of ZnCo2O4: add 0.25L of desalted water into the reactor, and adjust the pH of the solution to 8.5 with sodium carbonate; add the zinc nitrate-cobalt nitrate solution prepared in step 2.1 and the sodium carbonate solution prepared in step 2.2 into the reactor in parallel, control the stirring speed at 400 rpm during the neutralization process, control the pH of the solution at 8.8, add the feeding time for 7 minutes, and the reaction temperature at 63°C; after the solutions in step 2.1 and step 2.2 are added, continue to maintain the reaction temperature and stir and age for 90 minutes;

[0221] Step 2.4: After aging, the material is filtered and washed until the Na content in the material is less than 100 mg / kg;

[0222] Step 2.5, the washed material is dried at 110°C for 18 hours, and then heated to 850°C and calcined for 4 hours to obtain ZnCo2O4 spinel structure powder for use;

[0223] Step 3: Preparation of CeO2-modified Al2O3 carrier

[0224] Step 3.1, take 250g of cerium nitrate hexahydrate and add it to 4.8L of desalted water to obtain a Ce(NO3)3 metal concentration of 0.5mol / L, and heat it to 63°C for standby use;

[0225] Step 3.2, slowly add 1.7L of 20% ammonia water to the above solution, control the stirring speed at 150 rpm during the dropping process, and add ammonia water until the pH reaches 9; then add 396g of activated alumina powder under stirring; let it stand for 12h after adding alumina powder;

[0226] Step 3.3, filter the material after standing, and dry the filter cake at 120°C for 10 hours, then heat it to 500°C and calcine it for 5 hours to obtain CeO2-modified Al2O3 for later use;

[0227] Step 4: Preparation of catalyst powder

[0228] The CuAl2O4 spinel powder, ZnCo2O4 spinel powder, CeO2 modified Al2O3 carrier, polyester fiber and graphite prepared above were ball-milled together in a ratio of 30:15:60:2:3 until all the particles passed 200 meshes to obtain a catalyst material for later use;

[0229] Step 5: Catalyst molding

[0230] The catalyst material obtained above and water were mixed evenly at a ratio of 100:5, and qualified particles were prepared using a dry powder granulator, and finally pressed into a Φ11×9×2mm black seven-hole cylinder;

[0231] The pressed Φ11×9×2mm black seven-hole cylinder was cured under 1.2Mpa pressure steam for 12h;

[0232] Step 6: Catalyst Calcination

[0233] The pressed catalyst was calcined at 1100°C for 4 hours to obtain the finished catalyst.

[0234] Example 3

[0235] This embodiment provides a N2O emission reduction catalyst, which includes, by mass percentage, 17.5% CuO, 6.5% ZnO, 54.5% Al2O3, 13.5% Co2O3, and 8.0% CeO2.

[0236] The preparation method of the N2O emission reduction catalyst comprises:

[0237] Step 1: Preparation of CuAl2O4 spinel powder

[0238] Step 1.1, preparation of copper nitrate-aluminum nitrate solution: 160g copper nitrate trihydrate and 496g aluminum nitrate nonahydrate are added to 2.1L desalted water to obtain a Cu(NO3)2-Al(NO3)3 mixed solution with a metal concentration of 0.9mol / L, wherein the molar ratio of Cu to Al is 0.49, and the solution is heated to 63°C for standby use;

[0239] Step 1.2, preparation of sodium carbonate solution: 300 g of sodium carbonate was added to 3.3 L of desalted water to obtain a Na2CO3 concentration of 0.8 mol / L, and the solution was heated to 63°C for later use;

[0240] Step 1.3, preparation of CuAl2O4: add 0.5L of desalted water into the reactor, and adjust the pH value of the solution to 7 with sodium carbonate; add the copper nitrate-aluminum nitrate solution prepared in step 1.1 and the sodium carbonate solution prepared in step 1.2 into the reactor in parallel, control the stirring speed at 400 rpm during the neutralization process, control the pH value of the solution at 7.2, add the flow time for 25min, and the reaction temperature for 63°C; after the solutions in step 1.1 and step 1.2 are added, continue to maintain the reaction temperature, stir and age for 90min, and the stirring speed during stirring and aging is 75 rpm;

[0241] Step 1.4: After aging is completed, the material is filtered and washed until the Na content in the material is less than 100 mg / kg;

[0242] Step 1.5, the washed material is dried at 110°C for 18 hours, and then heated to 850°C and calcined for 4 hours to obtain CuAl2O4 spinel powder for use;

[0243] Step 2: Preparation of ZnCo2O4 spinel powder

[0244] Step 2.1, preparation of zinc nitrate-cobalt nitrate solution: 101 g of zinc nitrate hexahydrate and 141 g of cobalt nitrate hexahydrate were added to 0.65 L of desalted water to obtain a mixed solution of Zn(NO3)2-Co(NO3)2 with a metal concentration of 1.1 mol / L, wherein the molar ratio of Zu to Co is 0.7, and the solution was heated to 63°C for standby use;

[0245] Step 2.2, preparation of sodium carbonate solution: Preparation of sodium carbonate solution: Take 200g of sodium carbonate and add it into 2.1L of desalted water to obtain a concentration of Na2CO3 of 0.8mol / L, and heat it to 63°C for use;

[0246] Step 2.3, preparation of ZnCo2O4: add 0.25L of desalted water into the reactor, and adjust the pH of the solution to 8 with sodium carbonate; add the zinc nitrate-cobalt nitrate solution prepared in step 2.1 and the sodium carbonate solution prepared in step 2.2 into the reactor in parallel, control the stirring speed at 400 rpm during the neutralization process, control the pH of the solution at 8.6, add the feeding time for 7 minutes, and the reaction temperature at 63°C; after the solutions in step 2.1 and step 2.2 are added, continue to maintain the reaction temperature and stir and age for 90 minutes;

[0247] Step 2.4: After aging, the material is filtered and washed until the Na content in the material is less than 100 mg / kg;

[0248] Step 2.5, the washed material is dried at 110°C for 18 hours, and then heated to 850°C and calcined for 4 hours to obtain ZnCo2O4 spinel structure powder for use;

[0249] Step 3: Preparation of CeO2-modified Al2O3 carrier

[0250] Step 3.1, take 182g of cerium nitrate hexahydrate and add it to 0.85L of desalted water to obtain a Ce(NO3)3 metal concentration of 0.5mol / L, and heat it to 63°C for standby use;

[0251] Step 3.2, slowly add 1.25L of 20% ammonia water to the above solution, control the stirring speed at 150 rpm during the dropping process, and add ammonia water until the pH reaches 9; then add 288g of activated alumina powder under stirring; let it stand for 12h after adding alumina powder;

[0252] Step 3.3, filter the material after standing, and dry the filter cake at 120°C for 12 hours, then heat it to 500°C and calcine it for 5 hours to obtain CeO2-modified Al2O3 for later use;

[0253] Step 4: Preparation of catalyst powder

[0254] The CuAl2O4 spinel powder, ZnCo2O4 spinel powder, CeO2 modified Al2O3 carrier, polyvinyl alcohol and graphite prepared above were ball-milled together in a ratio of 30:15:60:2:3 until all the particles passed 200 meshes to obtain a catalyst material for later use;

[0255] Step 5: Catalyst molding

[0256] The catalyst material obtained above and water were mixed evenly at a ratio of 100:5, and qualified particles were prepared using a dry powder granulator, and finally pressed into a Φ11×9×2mm black seven-hole cylinder;

[0257] The pressed Φ11×9×2mm black seven-hole cylinder was cured under 0.8MPa pressure steam for 24h;

[0258] Step 6: Catalyst Calcination

[0259] The pressed catalyst was calcined at 1000°C for 6 hours to obtain the finished catalyst.

[0260] Example 4

[0261] This embodiment provides a N2O emission reduction catalyst, which includes, by mass percentage, 20% CuO, 4.9% ZnO, 57.1% Al2O3, 10% Co2O3, and 8.0% CeO2.

[0262] The preparation method of the N2O emission reduction catalyst is the same as that of Example 1.

[0263] Example 5

[0264] This embodiment provides a N2O emission reduction catalyst, which includes, by mass percentage, 25% CuO, 3% ZnO, 60% Al2O3, 6% Co2O3, and 6.0% CeO2.

[0265] The preparation method of the N2O emission reduction catalyst is the same as that of Example 1.

[0266] Example 6

[0267] This embodiment provides a N2O emission reduction catalyst and a preparation method thereof, wherein in step 1.1, the temperature is raised to 60° C. for standby use;

[0268] In step 1.2, heat to 60°C for later use;

[0269] Step 1.3, during the neutralization process, the stirring speed is controlled at 300 rpm, the addition time is 20 min, the reaction temperature is 60°C, and the stirring aging is 60 min, and the stirring speed during the stirring aging is 50 rpm;

[0270] In step 1.5, the washed material is dried at 100°C for 24 hours, and then heated to 800°C and calcined for 6 hours to obtain CuAl2O4 spinel powder for later use;

[0271] In step 2.1, heat to 60°C for later use;

[0272] In step 2.2, the temperature is raised to 60°C for later use;

[0273] In step 2.3, the stirring speed during the neutralization process was controlled at 300 rpm, the feeding time was 5 min, the reaction temperature was 60 ° C, and the stirring aging was 60 min;

[0274] In step 2.5, the washed material is dried at 120°C for 24 hours, and then heated to 800°C and calcined for 6 hours to obtain a ZnCo2O4 spinel structure powder for standby use;

[0275] In step 3.1, the temperature is raised to 60°C for later use;

[0276] In step 3.2, the stirring speed is controlled at 100 rpm during the dropwise addition process, and the mixture is allowed to stand for 10 h after the addition of the alumina.

[0277] In step 3.3, the filter cake is dried at 100°C for 12 hours, and then heated to 400°C for calcination for 6 hours to obtain CeO2-modified Al2O3 for later use;

[0278] In step 5, the pressed Φ11×9×2 mm black seven-hole cylinder is cured for 24 h under 0.8 MPa pressure steam conditions;

[0279] In step 6, the pressed catalyst is calcined at 1000° C. for 6 hours to obtain a finished catalyst. The rest is the same as in Example 1.

[0280] Example 7

[0281] This embodiment provides a N2O emission reduction catalyst and a preparation method thereof, wherein in step 1.1, the temperature is raised to 65° C. for standby use;

[0282] In step 1.2, heat to 65°C for later use;

[0283] Step 1.3, during the neutralization process, the stirring speed is controlled at 500 rpm, the addition time is 30 min, and the reaction temperature is 65°C; the stirring aging is 120 min, and the stirring speed during the stirring aging is 100 rpm;

[0284] In step 1.5, the washed material is dried at 120°C for 12 hours, and then heated to 900°C and calcined for 2 hours to obtain CuAl2O4 spinel powder for later use;

[0285] In step 2.1, heat to 65°C for later use;

[0286] In step 2.2, the temperature is raised to 65°C for later use;

[0287] In step 2.3, the stirring speed during the neutralization process was controlled at 500 rpm, the feeding time was 10 min, the reaction temperature was 65 ° C, and the stirring aging was 120 min;

[0288] In step 2.5, the washed material is dried at 120°C for 12 hours, and then heated to 900°C and calcined for 2 hours to obtain a ZnCo2O4 spinel structure powder for standby use;

[0289] In step 3.1, heat to 65°C for later use;

[0290] In step 3.2, the stirring speed is controlled at 200 rpm during the dropwise addition process, and the mixture is allowed to stand for 14 h after the addition of the alumina.

[0291] In step 3.3, the filter cake is dried at 140°C for 8 h, and then heated to 600°C for calcination for 4 h to obtain CeO2-modified Al2O3 for later use;

[0292] In step 5, the pressed Φ11×9×2 mm black seven-hole cylinder is cured for 24 h under 0.8 MPa pressure steam conditions;

[0293] In step 6, the pressed catalyst is calcined at 1100° C. for 4 hours to obtain a finished catalyst. The rest is the same as in Example 1.

[0294] Comparative Example 1

[0295] The catalyst prepared by CN201410174954.4 for high-temperature catalytic decomposition of N2O.

[0296] Comparative Example 2

[0297] A catalyst for high-temperature catalytic decomposition of N2O prepared in CN201610993255.1.

[0298] Comparative Example 3

[0299] Johnson Matthey's Yara58-1 catalyst.

[0300] Initial activity comparison:

[0301] Figure 2 The activity evaluation device of the catalyst of the examples and comparative examples of the present application is first loaded into the isothermal zone of the reactor with 3 mL of the catalyst samples of Examples 1-7 and Comparative Examples 1-3 (crushed into particles with a diameter of 1 to 2 mm) and loaded into a fixed bed reactor. The detection gas composition is 2000 ppm N2O, 6.7% O2, and the balance is N2. The detection pressure is normal pressure-0.04 MPa, the detection temperature is 860-870 ° C, and the detection raw gas space velocity is 40000, 60000, and 80000 h -1 , the test results are as follows:

[0302]

[0303] Under different space velocity conditions, the activities of Examples 1-7 are better than those of Comparative Examples 1 and 2, and are basically equivalent to Comparative Example 3, indicating that the initial activity of the catalyst is good.

[0304] Activity comparison under hydrothermal conditions:

[0305] 3 mL of each catalyst sample (crushed into particles with a diameter of 1 to 2 mm) of Examples 1 to 7 and Comparative Examples 1 to 3 were loaded into a fixed bed reactor. The test gas composition was 2000 ppm N2O, 6.7% O2, 20% H2O, and the balance was N2. The test pressure was normal pressure - 0.04 MPa, the test temperature was 860-870°C, and the test raw gas space velocities were 40000, 60000, and 80000 h-1, respectively. -1 , the test results are as follows:

[0306]

[0307] After adding water vapor to the raw gas, under different space velocity conditions, the activity of Example 1-7 is better than that of Comparative Example 1-3, indicating that the catalyst has higher and more stable activity under water vapor conditions and is more suitable for actual working conditions.

[0308] Activity comparison after 100h continuous operation:

[0309] 3 mL of each catalyst sample of Example 1 and Comparative Examples 1-3 (crushed into particles with a diameter of 1-2 mm) were loaded into a fixed bed reactor. The detected gas composition was 2000 ppm N2O, 6.7% O2, 20% H2O, and the balance was N2. The detected pressure was normal pressure-0.04 MPa, the detected temperature was 860-870°C, and the detected raw gas space velocity was 60000 h -1 , continuous testing for 100h, the inspection results are as follows:

[0310]

[0311]

[0312] From the comparison of the continuous operation for 100 hours, it can be found that the activity stability of the catalyst in Example 1 is significantly better than that in Comparative Examples 1-3.

[0313] Lateral pressure mechanical strength test results

[0314] The catalysts prepared in Examples 1-7 of the present invention were subjected to a lateral pressure mechanical strength test, with Comparative Examples 1-3 being used as comparative samples. The results are shown in Table 4:

[0315] Table 4 Lateral pressure mechanical strength test results

[0316] name Sample lateral pressure mechanical strength / N / cm Example 1 89 Example 2 97 Example 3 103 Example 4 86 Example 5 90 Example 6 92 Example 7 81 Comparative Example 1 83 Comparative Example 2 85 Comparative Example 3 61

[0317] It can be seen from Table 4 that the lateral pressure mechanical strength of the catalyst prepared in Examples 1-7 is comparable to that of Comparative Examples 1-2, and is better than that of Comparative Example 3. The high mechanical strength is beneficial to the catalyst not being easy to break or pulverize during use, and can effectively increase the operating cycle of the catalyst.

[0318] Catalyst heat-resistant shrinkage results

[0319] The catalysts prepared in Examples 1-7 of the present invention and the samples in Comparative Examples 1-3 were subjected to a catalyst heat-resistant shrinkage test. The catalysts were calcined at 1300° C. for 3 hours in a muffle furnace and then the shrinkage of the catalyst particles was tested. The test results are shown in Table 5:

[0320] Table 5 Catalyst heat-resistant shrinkage results

[0321] name Radial shrinkage / % Axial shrinkage / % Example 1 2.2 1.5 Example 2 2.5 1.7 Example 3 2.1 1.3 Example 4 2.5 1.6 Example 5 2.6 1.4 Example 6 2.4 1.5 Example 7 2.7 1.6 Comparative Example 1 2.9 2.1 Comparative Example 2 3.3 2.5 Comparative Example 3 5.3 4.7

[0322] It can be seen from Table 5 that the catalysts prepared in Examples 1-7 have lower radial and axial shrinkage rates than those in Comparative Examples 1-3, and the surface catalysts have better thermal stability and are more suitable for high-temperature operation.

[0323] The N2O emission reduction catalyst and its preparation method provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A N2O emission reduction catalyst, characterized in that: The catalyst includes CuO, ZnO, Al2O3, CoO, and CeO2.

2. The N2O emission reduction catalyst according to claim 1, characterized in that: In terms of mass percentage, the catalyst includes 15% to 25% CuO, 3% to 8% ZnO, 50% to 70% Al2O3, 5% to 15% Co2O3, and 5% to 15% CeO2.

3. A method for preparing a catalyst for reducing N2O emissions, characterized in that: include: Providing desalted water, adjusting the pH to 7-8, and obtaining a first solution; A copper nitrate-aluminum nitrate mixed solution and a sodium carbonate solution are provided respectively, and the copper nitrate-aluminum nitrate mixed solution and the sodium carbonate solution are added to the first solution in parallel to obtain a second solution, and then subjected to a second stirring aging, a first filtration, a first washing, a first drying and a first calcination to obtain a CuAl2O4 spinel powder; Providing desalted water, adjusting the pH to 8-9, and obtaining a third solution; A zinc nitrate-cobalt nitrate mixed solution and a sodium carbonate solution are provided respectively, and the zinc nitrate-cobalt nitrate mixed solution and the sodium carbonate solution are added to the third solution in parallel to obtain a fourth solution, and then subjected to a fourth stirring aging, a second filtration, a second washing, a second drying and a second calcination to obtain a ZnCo2O4 spinel powder; Provide a Ce(NO3)3 solution, slowly drop an alkali solution into the Ce(NO3)3 solution until the pH reaches 9-10, then add activated alumina powder under the sixth stirring, let stand, then filter for a third time, dry for a third time and calcine for a third time to obtain a CeO2-modified Al2O3 carrier; The CuAl2O4 spinel powder, the ZnCo2O4 spinel powder, the CeO2-modified Al2O3 carrier, the binder and the graphite are ball-milled and sieved together to obtain a catalyst material; The catalyst material is mixed with water, pressed, steam cured, and calcined for the fourth time to obtain a finished catalyst product.

4. The method for preparing the N2O emission reduction catalyst according to claim 3, characterized in that: When preparing CuAl2O4 spinel powder, adjust the pH to 7-8 with sodium carbonate; and / or When preparing ZnCo2O4 spinel powder, adjust the pH to 8-9 with sodium carbonate; and / or The pH of the second solution is 7 to 7.5; and / or The pH of the fourth solution is 8.5-9.

5. The method for preparing the N2O emission reduction catalyst according to claim 3, characterized in that: The preparation method of the copper nitrate-aluminum nitrate mixed solution comprises taking copper nitrate trihydrate and aluminum nitrate nonahydrate and adding them into desalted water to obtain a Cu(NO3)2-Al(NO3)3 mixed solution; the first metal concentration in the Cu(NO3)2-Al(NO3)3 mixed solution is C1, the molar ratio of Cu to Al in the Cu(NO3)2-Al(NO3)3 mixed solution is M1, and the Cu(NO3)2-Al(NO3)3 mixed solution is heated to T1; and / or Providing desalted water and sodium carbonate, adding sodium carbonate to the desalted water to obtain a Na2CO3 solution; the concentration of the Na2CO3 solution is C2, and the Na2CO3 solution is heated to T2; and / or The time of the first parallel addition is t1, the speed of the first stirring during the first parallel addition is v2, the reaction temperature during the first parallel addition is T2, the temperature is maintained at T3 after the first parallel addition, the speed of the second stirring aging is v3, the time of the second stirring aging is t2, the first washing is until the Na content is lower than C3, the temperature of the first drying is T4, the time of the first drying is t3, the temperature of the first calcination is T5, and the time of the first calcination is t4; and / or The method for obtaining a zinc nitrate-cobalt nitrate mixed solution comprises taking zinc nitrate hexahydrate and cobalt nitrate hexahydrate and adding them to desalted water to obtain a Zn(NO3)2-Co(NO3)2 mixed solution; the concentration of the second metal in the Zn(NO3)2-Co(NO3)2 mixed solution is C4, the molar ratio of Zn to Co in the Zn(NO3)2-Co(NO3)2 mixed solution is M2, and the Zn(NO3)2-Co(NO3)2 mixed solution is heated to T6; and / or Providing desalted water and sodium carbonate, adding sodium carbonate to the desalted water to obtain a Na2CO3 solution; the concentration of the Na2CO3 solution is C5, and heating the Na2CO3 solution to T7; and / or The time of the second parallel addition is t5, the speed of the third stirring during the second parallel addition is v5, the reaction temperature during the second parallel addition is T7, the temperature is maintained to T8 after the second parallel addition is completed, the speed of the fourth stirring aging is v6, the time of the fourth stirring aging is t6, the second washing is until the Na content is lower than C6, the temperature of the second drying is T9, the time of the second drying is t7, the temperature of the second calcination is T10, and the time of the second calcination is t8; and / or Adding cerium nitrate hexahydrate to desalted water to obtain a Ce(NO3)3 solution; the concentration of the third metal in the Ce(NO3)3 solution is C7, and the Ce(NO3)3 solution is heated to T13; and / or During the process of adding the alkali solution, a fifth stirring is performed, the speed of the fifth stirring is v7, the speed of the sixth stirring is v8, the standing time is t9, the temperature of the third drying is T11, the time of the third drying is t10, the temperature of the third calcination is T12, and the time of the third calcination is t11; and / or Curing the pressed catalyst sample under P pressure steam conditions for T12; and / or The temperature of the fourth calcination is T14, and the time of the fourth calcination is t13.

6. The method for preparing the N2O emission reduction catalyst according to claim 5, characterized in that: C1 is 0.9mol / L~1.1mol / L; and / or M1 is 0.4~0.5; and / or T1 is 60℃~65℃; and / or C2 is 0.6~0.8mol / L; and / or T2 is 60℃~65℃; and / or t1 is 20min~30min; and / or v2 is 300rpm~500rpm; and / or T2 is 60℃~65℃; and / or T3 is 60℃~65℃; and / or v3 is 50rpm~100rpm; and / or t2 is 60min~120min; and / or C 3 is 100 mg / kg; and / or T4 is 100℃~120℃; and / or t3 is 12h~24h; and / or T5 is 800℃~900℃; and / or t4 is 2h~6h; and / or C4 is 0.9mol / L~1.1mol / L; and / or M2 is 0.5~0.7; and / or T6 is 60℃~65℃; and / or C5 is 0.6mol / L~0.8mol / L; and / or T7 is 60℃~65℃; and / or t5 is 5min~10min; and / or v5 is 300rpm~500rpm T7 is 60°C to 65°C; and / or T8 is 60°C to 65°C; and / or v6 is 50 rpm to 100 rpm; and / or t6 is 60min to 120min; and / or C6 is 100 mg / kg; and / or T9 is 100°C to 120°C; and / or t7 is 12h to 24h; and / or T10 is 800°C to 900°C; and / or t8 is 2h to 6h; and / or C7 is 0.4 mol / L to 0.5 mol / L; and / or T13 is 60℃~65℃; and / or v7 is 100 rpm to 200 rpm; and / or V8 is 300 rpm to 500 rpm; and / or t9 is 10h to 14h; and / or T11 is 100°C to 140°C; and / or t10 is 8h to 12h; and / or T12 is 400°C to 600°C; and / or t11 is 4h to 6h; and / or P is 0.8MPa to 1.2MPa; and / or t12 is 12h to 24h; and / or T14 is 1000°C to 1100°C; and / or t13 is 4h~6h.

7. The method for preparing the N2O emission reduction catalyst according to claim 3, characterized in that: CeO2:Al2O3 in a mass ratio of 2:8; and / or The mass ratio of CuAl2O4 spinel powder, ZnCo2O4 spinel powder, CeO2 modified Al2O3 carrier, binder and graphite is 35-45:10-20:40-55:2:3; and / or The mass ratio of catalyst material to water is 100:3-5; and / or The alkali solution is ammonia water, and the concentration of ammonia water is 10% to 20%; and / or The mesh size for sieving is 180-220 mesh.

8. The method for preparing the N2O emission reduction catalyst according to claim 3, characterized in that: The adhesive includes one or more of kapok, polyvinyl alcohol and polyester fiber.

9. The method for preparing the N2O emission reduction catalyst according to claim 3, characterized in that: The average particle size of CuAl2O4 spinel is 10nm to 50nm; and / or The average particle size of ZnCo2O4 spinel is 30nm~100nm.

Citation Information

Patent Citations

  • Catalyst for directly decomposing N2O and preparation method of catalyst

    CN102962073A

  • Catalyst for performing high-temperature catalytic decomposition of N2O and preparation method of catalyst

    CN103949264A

  • Preparation technology of catalyst used for high temperature catalytic decomposition of N2O

    CN106391037A

  • Method for reducing nitrous oxide in gases and corresponding catalysts

    CN1274297A

  • Catalyst for decomposing N2O, its use and method for prodn. thereof

    CN1398196A